Serial Mediation of Digital Literacy and Managerial Ability Towards The Relationship Between Managerial Characteristics and Bumdes Performance Abstract - Sudarmiani; Elly Astuti; FX Sri Sadewo; Yuliani Tutik; Risa Wahyuni EDT (INVENTORY: JURNAL AKUNTANSI, 2026)
BUMDes is a business unit at the village level that aims to build economic independence by improving the welfare of its people. However, the achievement of this goal still needs to be met due to its limited resources. As a result, BUMDes business operational activities could be improved due to difficulties in determining its business roadmap. This study aims to test age, education level, and experience managing BUMDes as a proxy for managerial characteristics in improving BUMDes performance. This study uses two mediating variables, namely digital literacy and managerial ability. The study's results indicate managerial characteristics cannot directly affect BUMDes performance. The results of the serial mediation test indicate that managerial characteristics can indirectly affect BUMDes performance through digital literacy and managerial ability.